Social Skills, Autonomy and Communication in Children with Autism - Sălceanu, Claudia; Lăcătuș, Lucia (Technium Social Sciences Journal, 2022)
The number of people with autism spectrum disorder is growing at an accelerated rate from year to year. Unlike 20 or 30 years ago, when few people in the general population had ever heard of autism, now you rarely meet a person who has not heard of this disorder and does not know anyone with a relative diagnosed with ASD. A sample of 30 children with ASD was assessed with Adaptive Behavior Assessment System II (ABAS II), a Screening of personal autonomy skills from PEDa (Cognitrom, Cluj-Napoca) and a Screening of social skills from PEDa (Cognitrom, Cluj-Napoca). Our main objectives were: (O1) Identifying the correlations between personal autonomy, social skills, and communication in children with autism spectrum disorders, and (O2) Identifying the differences between personal autonomy, social skills, and communication according to the sex of children with autism spectrum disorder. The hypotheses of our study are: (1) It is assumed that there is a correlation between social skills and communication in children with autism spectrum disorder; (2) It is assumed that there is a correlation between communication and personal autonomy in children with autism spectrum disorder; (3) It is assumed that there is a difference in personal autonomy depending on the sex of children with ASD; (4) It is assumed that there is a difference in social skills according to the sex of children with ASD; (5) It is assumed that there is a difference in the development of communication according to the sex of children with ASD. Results show the existence of a relationship between communication, social skills, and personal autonomy, and we also obtained differences based on gender in social skills. In terms of personal autonomy and communication, although some differences were obtained, they were not statistically significant. Results are discussed in the context of the importance of personalized interventions plans for children with ASD.